2022
DOI: 10.1136/bmjopen-2022-064949
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation willingness for institutional care by the disabled elderly and its influencing factors based on Andersen’s model: a cross-sectional survey of Henan, China

Abstract: ObjectiveTo explore the factors that influence institutional care for the disabled elderly in China and the key factors that influence individuals based on the Andersen model.DesignCross-sectional survey.SettingThe research was conducted in 18 cities in Henan Province, China.Main outcome measuresA multistage, stratified sampling design was employed. The χ2test was used to compare the differences in basic information of the disabled elderly. A binary Logit model was used to examine the factors influencing the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Second, social support and family relationships have a significant impact on the willingness of older adults individuals to receive care ( 45 ). The presence of close family relationships ( 46 ), support from children or other relatives ( 47 ), living arrangements with spouses and children ( 48 , 49 ), proximity to children ( 50 ), community support and services ( 51 ), interpersonal relationships, and spiritual needs ( 52 ) can influence individuals’ willingness to receive care. Additionally, the individual characteristics of older adults people also play a role in their willingness to receive care.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, social support and family relationships have a significant impact on the willingness of older adults individuals to receive care ( 45 ). The presence of close family relationships ( 46 ), support from children or other relatives ( 47 ), living arrangements with spouses and children ( 48 , 49 ), proximity to children ( 50 ), community support and services ( 51 ), interpersonal relationships, and spiritual needs ( 52 ) can influence individuals’ willingness to receive care. Additionally, the individual characteristics of older adults people also play a role in their willingness to receive care.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang [ 13 ] found the willingness of the elderly to enter the nursing institution is influenced by individual, family environment and community environment, including age, living with spouse and children, house ownership and availability of home healthcare services. Yang found living alone, medical payment, mental illness were the influencing factors of the disabled elderly to receive institutional care [ 14 ]. A study conducted in 7 cities in China indicated that intergenerational family support is a significant driver on the willingness of the old people to choose nursing care.…”
Section: Introductionmentioning
confidence: 99%
“… 7 However, in Chinese families, children’s ability to care for elderly adults has been eroded by demographic changes and socioeconomic development. 8 The younger generation has had to move to cities to work, which means that family-centred forms of care for elderly individuals are gradually disappearing 9 ; thus, there is an inevitable growing demand for institutional care. To cope with the growth of a rapidly ageing population, the Chinese government has released a blueprint for an emerging ageing service and support network that aims to establish a social ageing system of home-based ageing with community-based ageing as the necessary support and institutionalised ageing as a supplement.…”
Section: Introductionmentioning
confidence: 99%